The Impact of Tourism Activities on Carbon Emissions: Evidence Using a Time-Varying Parameter Vector Autoregression Model - A. Nazif Çatık; Esra Ballı; Coşkun Akdeniz; Cihan Çobanoğlu; Mohamad Husam Helmi (İktisat Politikası Araştırmaları Dergisi)
This article examines the impact of tourism activities, economic growth, and energy demand on environmental degradation in Turkey using Primiceri’s (2005) time-varying parameter structural vector autoregression model for the period 1991:Q1 to 2020:Q1. The findings from the linear VAR model indicate that the response of carbon emissions to shocks in tourism activity is negative and significant. However, the time-varying responses show that the impact of tourism activities on environmental degradation varies over time but is not significant for most analysis period. The insignificant impact of tourism on carbon emissions implies that the tourism sector can be supported by policymakers without harming the environment. Furthermore, our findings on the positive and significant timevarying impact of tourism activities on economic growth support the validity of the tourism-led growth hypothesis.